Effects of Menstrual Cycles on VOR Gain Functions - Sinha, Sujeet Kumar; Mohamad, Alfarghal; Penwal, Suman (Annals of Otology and Neurotology, 2021)
Purpose The aim of the present study was to assess the vestibuloocular reflex (VOR) gain function and VOR gain asymmetry during the various phases of the menstrual cycle in young healthy female participants. The study also aimed to characterize the presence or absence of corrective saccades during the various phases of the menstrual cycle.Method Twenty-nine young healthy females participated in the study. The video head impulse test (vHIT) was performed in lateral, left anterior right posterior, and right anterior left posterior plane during the various phases of the menstrual cycle to see the changes in VOR gain function and VOR gain asymmetry ratio changes.Results A repeated measure analysis of variance test did not show any significant main effect for the VOR gain function and VOR gain asymmetry ratio in various phases of the menstrual cycle in all the participants. The result suggested no changes in VOR gain function and VOR asymmetry ratio in healthy females during the menstrual cycle. Also, there was an absence of saccades in the entire participants group during the various phases of the menstrual cycle.Conclusions As the VOR gain function does not change during the various phases of the menstrual cycle in young healthy females, there is no need to consider the various phases of the menstrual cycle while testing any female participant during the vHIT test.
Keywords: video head impulse test; menstruation cycle; VOR gain